PENGARUH ASIMETRI INFORMASI, CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA: THE EFFECT OF INFORMATION ASYMMETRY, CORPORATE SOCIAL RESPONSIBILITY, COMPANY SIZE AND OWNERSHIP STRUCTURE ON PROFIT MANAGEMENT - Hadi, Yudha Asmara; Nasir, Azwir; Hasan, Mudrika Alamsyah (Universitas Riau, 2024)
This study aims to find empirical evidence related to the Effect Analysis of Information Asymmetry, Corporate Social Responsibility, Company Size and Ownership Structure on Profit Management in Primary Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2021 period. The population of this study is Companies in the Primary Consumer Goods Sector Listed on the Indonesia Stock Exchange for the 2019-2021 period. The research sample was selected using the purposive sampling method. The sample determination was predetermined based on the criteria. Hypothesis testing was carried out with the help of the SPSS 26 statistical test tool. The results of this study indicate that information asymmetry has a positive effect on earnings management, corporate social responsibility has no effect on earnings management, size has a positive effect on earnings management, institutional ownership has no effect on earnings management and managerial ownership has no effect on earnings management.